Exploration of defatted waste feed stock for the continuous production of biomethane under psychrophilic outdoor conditions. Issue 3 (6th March 2017) - Singhal, Shailey; Sharma, Rajan; Agarwal, Shilpi; Arora, Shefali; Singhal, Naveen
Abstract : The present work focuses on the bio‐methane production potential of jatropha defatted waste (JDFW) in batch type continuous stirred tank reactor (CSTR). JDFW was codigested with cow dung (CD) as inoculum in various ratios. 75:25 ratio of JDFW and CD with carbon to nitrogen (C/N) ratio 12:1 was chosen as the optimum to run in CSTR. 65–69% methane was obtained in 0.184m 3 of biogas per kg of total solid in only 15 days. The efficient energy gain and reduction in hydraulic retention time (HRT) of bio‐methane production process was successfully accomplished by minimizing the usage of fresh water and external nutrients. The integration of anaerobic digestion with CSTR could maintain the sustainability of biomethane production, and also significantly reduced the HRT of the process. © 2017 American Institute of Chemical Engineers Environ Prog, 36: 845–849, 2017